생약 복합 추출물의 인간 골수 유래 중간엽 줄기세포에서의 골 분화에 미치는 영향 - 김다솔; 성기수; 박민성; 김미경; 박경은; 곽연주; 윤금정; 김형준; 배문경; 배수경; 장혜옥 (대한구강악안면병리학회지, 43(5), 2019)
Herbal medicine has been the basis for medical treatments through much of human history, and such traditional medicine is still widely practiced today. Modern medicine makes use of many plant-derived compounds as the basis for pharmaceutical drugs. In traditionally, Achyranthes aspera, Safflower (Carthamus tinctorius) seed and Acanthopanax senticosus have been used for the treatment and prevention of bone-related diseases. In this study, we investigated the pharmacological effect of mixture of Achyranthes aspera, Safflower (Carthamus tinctorius) seed and Acanthopanax senticosus and the other herbs. Two types of enzymes were used to enhance the extraction components of amino acid, mineral content, free sugar, and flavor recovery in extracting natural herbal mixtures(NME). We evaluated regulation of osteogenic differentiation in human bone marrow mesenchymal stem cells using alkaline phosphatase staining, alizarin red S staining and RT-PCR. The CCK-8 assay indicated that NME had no cytotoxicity but increased cell survival. In addition, NME promoted the mineralization and expression of osteogenic differention marker genes in human bone marrow mesenchymal stem cells. Therefore, NME has an effect of promoting proliferation and osteogenic differentiation of human mesenchymal stem cell. KCI Citation Count: 0